Multispectral images segmentation using fuzzy probabilistic local cluster for unsupervised clustering - Mantilla S.C.L. (2018)
The authors would like to CONCYTEC (Consejo Nacional de Ciencia, Tecnolog ıa e Innovacion Tecnoloogica ), FONDE- ´ CYT (Fondo Nacional de Desarrollo Cient´ıfico y Tecnologico) ´and ANA (Autoridad Nacional del Agua) for satellite imagesand supporting this project